Pengaruh Audit Tenure dan Komite Audit Terhadap Kualitas Laba Pada Perusahaan Manufaktur yang Terdaftar Di Bursa Efek Indonesia Tahun 2009-2011 - Sayuthi Sayuthi (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2017)
This study aims to provide empirical evidence on the effect of audit tenure and audit committee to earning of quality. The research was conducted at a manufacturing company listed on the Indonesia Stock Exchange in 2009-2011. This type of study is a research verificative or hypothesis testing research. The research method used in this research is census and balanced panel data. Target population in this study is a manufacturing company that has complete data for all variables studied. The population of this study is 39 firms which observed periods are 3 years. The data collection techniques using secondary data from financial statements have been audited and published www.idx.co.id obtained from website to the financial statements in the period 2009-2011. The hypothesis is tested by using multiple regression analysis. This result shows that (1) when there is not audit tenure and audit committee, earning of quality is at 95,4% and is not at 100% (2) audit tenure and audit committee simultaneously have negative influence toward earning of quality (3) Audit tenure and audit committee partially has negative influence toward earning of quality.